Випробування показників безпеки ручного електроінструменту - Єрмак, А. Р. (My University, 2020)
The essence, goals, tasks and content of the conformity assessment of a hand-held power tool are considered. Regulatory documents are proposed to test safety parameters. The program of testing of safety parameters is developed. Test methods are proposed. Testing and testing equipment for testing safety parameters is offered. Test results are given
Keywords: електроінструмент